New pharmaceuticals in inflammatory bowel disease - Łodyga, Michał; Eder, Piotr; Bartnik, Witold; Gonciarz, Maciej; Kłopocka, Maria; Linke, Krzysztof; Małecka-Panas, Ewa; Radwan, Piotr; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
This paper complements the previously published Guidelines of the Working Group of the Polish Society of Gastroenterology and former National Consultant in Gastroenterology regarding the management of patients with Crohn’s disease and ulcerative colitis. Attention was focused on the new pharmaceutical recently registered for inflammatory bowel disease treatment.